The Employee Model of Self-Employment - Świątkowski, Andrzej Marian (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The author considers the legitimacy of constructing a new concept of employment of self-employed natural persons. It is based on the regulations of the speciﬁc status of these people who perform this type of work in some Member States of the European Union introduced into the labour law. He is analyzes the basics and criteria used by the judicature of the Court of Justice of the EU. It focuses on a speciﬁc and real sole proprietorship, consisting in the paid provision of services performed for and under the direction of another person – employer/entrepreneur or entity. He comes to the conclusion that there is no need to construct complex, separate legal concepts in which self-employed persons could act as “employees.”